Technical Guidance for Environmental Management Efforts at Nature School of Le Cendekia to achieve Adiwiyata - Nurul Masyiah Rani Harusi; Rasdiana Zakaria; Irwan Ridwan Rahim; Ibrahim Djamaluddin; Fakhruddin . (Faculty of Engineering UNHAS, 2024)
In the context of efforts to achieve Adiwiyata status at Le Cendekia Boarding School, the Department of Environmental Engineering at Hasanuddin University (UNHAS) has organized a technical guidance program. This program is an annual activity that focuses on environmental management and aims to increase environmental awareness among students and realize an environmentally conscious school. The technical guidance activities cover various topics such as Adiwiyata, drinking water management, wastewater management, waste management, biogas production, and the importance of green open spaces. During the program, Pre-Test and Post-Test assessments were conducted on 17 students to measure their understanding before and after receiving the information. Additionally, field visits to Le Cendekia Boarding School were conducted to observe the practical implementation of environmental practices, including waste management, eco enzyme production, garden produce, and livestock. The results of the Pre Testshowed an average score of 51.18, while thePost Test average score was 64.71. This activity demonstrates an improvement in students' understanding and awareness of environmental issues and practical solutions that can be implemented to preserve the environment. The technical guidance program is expected to support Le Cendekia Boarding School in its efforts to achieve Adiwiyata School status and promote sustainable environmental awareness.